Exploring the Borrowing Words in English Language Learning: A Case Study of Universitas Islam Riau Students - Rugaiyah, Rugaiyah; Ariyanto, Joko (LP. Ma'arif Janggan Magetan, 2025)
This research aims to assess the understanding of English-borrowing words among fifth-semester students at Universitas Islam Riau, Pekanbaru. The methodology employed involved a test consisting of 30 questions, categorized into three types: 10 questions each for loanwords, blend words, and loan shifts. A total of 50 students from the fifth semester of English language in the academic year 2023/2024 participated in the study, providing insights into their vocabulary comprehension. The findings revealed that the term